Influence of Inula helenium rhizomes and Matricaria chamomilla inflorescences on the biochemical and physiological parameters in male rats fed a high-fat diet - Maryna Lieshchova; Valentyn Yefimov; Victor Brygadyrenko (National Institute of Public Health - National Institute of Hygiene, 2023)
Background. Pharmacological correction of a high-fat diet is of great interest to prevent the development of obesity and hypertension. More and more research is being done on the preventive use of medicinal herbs for excess caloric intake. Objective. The aim of this study was to determine the general physiological effect of I. helenium rhizomes and M. chamomilla inflorescences used in the diet of male rats consuming excess amounts of fat and calories in the daily diet. Material and methods. In a 30-day experiment, we determined the effect of I. helenium rhizome and M. chamomilla on the physiological activity and metabolic processes of laboratory rats consuming a high-fat diet. The physical activity was evaluated according to the mass gain of animals and change in the relative mass of the internal organs, and also the functional conditions of the central nervous system. The influence on the metabolic processes was revealed by biochemical and clinical blood analyses. Results. In a laboratory experiment on male rats, it was found that the addition of dry crushed rhizomes of Inula helenium L. and inflorescences of Matricaria chamomilla L. to the diet caused opposite changes in body weight. In the control group, the animals slightly increased their body weight (up to 111.5% of the initial weight by the end of the experiment); the rhizomes of I. helenium caused a decrease in body weight gain (up to 105.5% on the 30th day of the experiment compared to the initial weight); rats fed M. chamomilla inflorescences gained 123.2% of their initial body weight during the month of the experiment. The rhizomes of I. helenium caused an increase in the stomach relative mass. A decrease in the thymus relative weight was observed when animals were fed M. chamomilla inflorescences. The rhizomes of I. helenium stimulated an increase of blood protein concentration (mainly due to globulins), an increase in the alkaline phosphatase activity and cholesterol, and a decrease in the triglycerides concentration. M. chamomilla inflorescences reduced the blood urea concentration and increased the activity of alkaline phosphatase, causing strong changes in fat metabolism. Under the influence of the diet with the addition of M. chamomilla inflorescences, the atherogenic index increased in animals by 6.5 times relatively to the control group (due to a decrease in the concentration of high-density lipoprotein cholesterol and an increase in the concentration of low-density lipoprotein cholesterol, an increase in the total cholesterol concentration). When M. chamomilla was added to the diet, the blood triglycerides concentration in animals decreased sharply and the concentration of leukocytes increased. The concentration of monocytes exceeded the limits of the physiological norm both in the control group and in the group of animals fed on M. chamomilla inflorescences. Conclusions. The results of the studies show the promise for further research of I. helenium rhizomes in the prevention of hypertension and also indicate strong risks when using M. chamomilla inflorescences for preventive purposes during high-fat and hypercaloric diet.